Jardins dessinés et dessins de jardin - Catherine Fricheau (Projets de Paysage)
The article goes back on the designation « architecture garden» which usually qualifies the French garden from the 17th century. It shows the importance that the ocular knowledge takes both in the field construction and in its conception à a knowledge developed all through that century thanks to the applied sciences that are perspective, optics, and practical geometry. Indeed, the space of the classical garden appears to depend much more on a perfectly trained « eye judgment» than on the control conferred to the « architectural project» by the metrical accuracy of the plan.